(untitled) (Fiep Bulletin - online, 2014)
Study contributes to problems of game performance in soccer. The study is focused to tactics in soccer, exactly to improving tactical performances of players. Teams which play effective are more successful. But the tactics is multi-factoring phenomenon, which consist from tactical abilities, tactical skills and cognitive abilities. The aim of study was to find out the impact of different programs on soccer players´ tactical performance. The sample consists of 19 years old players. We compared changes in tactical performance between two groups after 15 weeks of two different training programs. First group realised program which consisted from higher proportionality of more difficult exercises and second group realised program consisted from higher proportionality of simpler exercises. The proportionality of more difficult exercises in first group was 35% of game situations (from 1 vs. 1 to 8 vs. 8, etc.) and proportionality of simpler exercises, like a drill exercise, in second group was only 15% of game situations (from 1 vs. 1 to 8 vs. 8, etc.). We evaluated selected components of tactics, such as: level of tactical knowledge, speed of decision-making, level of tactical performance in training and in the match. For comparison we used Mann-Whitney U-test. We found only one significant differences of tactical performance between groups favour first group, and it was only in level of tactical performance in training (p<0.05). In the other evaluation we did not find out significant differences. Acknowledgement: This study is a part of VE GA grant No. 1/1252/12: “Improvement of identification and selection system of young male talented soccer players for junior national teams in the Slovak Republic and streamlining the content of their training and preparation.”